ROLE OF PUBLIC LIBRARY READER EMOTIONAL IN MOULDING AND HEALING: A BIBLIOTHERAPHICAL CASE STUDY - S, ARAVIND; R, KAVITHA (International Journal of Psychosocial Rehabilitation, 2020)
Bibliotherapy has been widely recognized as an approach that helps librarians to better address emotional, behavioral and social concerns. In the Indian context, bibliotherapy is still new, by conceptualizing bibliotherapy in a public library. The study will provide a better understanding of concepts bibliotherapy and make recommendations to the librarian by providing a description of and a rationale for the use of bibliotherapy by public libraries.139 responses received from public library readers of a chosen Central library and Selected Branch libraries in Dindigul Town. The convenience sampling techniques were used. It is observed that more than half of the readers frequently read books like Poetry, Novels, Short stories and Motivational Books. 99 of the respondents (71.22%) feel Difficulty in choosing the right self-help book. Two-third of the respondents strongly agree that reading self-help books 'Enable me to change my perspective towards life as I observe life from a different angle' (69.19%), 'Inspire me to make better choices' (64.3%). Further studies may be undertaken in other environments like schools, universities, working places, etc., to get a real picture of the effect of bibliotherapy.